Effect of Vitamin D Supplementation on Bone Fracture Healing: Impact on Healing Rates, Recovery Time, and Functional Recovery - Beatarisa, Caera; Qaissara, Elvaretta (International Journal on Health and Medical Sciences, 2024)
This study examines the effect of vitamin D supplementation on bone fracture healing, focusing on its ability to improve healing rates, reduce time to union, and enhance functional recovery. A deficiency in vitamin D is linked to slower bone healing and higher risk of complications, particularly in individuals with limited sun exposure or osteoporosis. The research demonstrates that vitamin D supplementation can significantly accelerate bone healing, making it a valuable intervention in fracture care. The findings suggest that incorporating vitamin D into clinical guidelines could optimize patient outcomes, particularly in vulnerable populations such as the elderly. However, further research is needed to establish the optimal dosage, duration, and long-term effects of vitamin D supplementation. This approach has the potential to reduce healthcare costs by minimizing complications and improving overall fracture recovery, making it a cost-effective and accessible solution in clinical settings. The study highlights the importance of addressing vitamin D deficiency in fracture patients and the potential for improved patient quality of life and bone health.